Defining Vascular Stem Cells - Lin, Ching-Shwun (Mary Ann Liebert, Inc., 2013)
Mesenchymal stem cells (MSCs) exist in most adult tissues and have been located near or within blood vessels. Although “perivascular” has been commonly used to describe such locations, increasing evidence points at the vessel wall as the exact location. Thus, “vascular stem cells (VSCs)” is recommended as a more accurate term for MSCs. Furthermore, 2 cell populations, namely pericytes and adventitial progenitor cells (APCs), are the likely VSCs. The pericyte evidence relies on the so-called pericyte-specific markers, but none of these markers is pericyte specific. In addition, pericytes appear to be too functionally diverse and sophisticated to have a large differentiation capacity. On the other hand, APCs are more naïve functionally and, therefore, more akin to being VSCs. In vitro, these cells spontaneously differentiate into pericytes, and can be induced to differentiate into vascular cells (endothelial and smooth muscle cells) and mesenchymal cells (eg, bone, cartilage, and fat). In vivo, indirect evidence also points to their ability to differentiate into mesenchymal cells of their native tissue (eg, fat). Moreover, they possess a large paracrine capacity and, therefore, can help maintain tissue homeostasis by encouraging the replication and differentiation of mesenchymal cells locally. These proposed in vivo functions are areas of interest for future research on VSCs.